Jackpot Justice: The Value of Inefficient Litigation - Jun Zhou (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Litigation seems to be a Pareto-ineffcient outcome of pretrial bargaining; however, this paper shows that litigation can be the outcome of rational behavior by a litigant and her attorney. If the attorney has more information than his client concerning the characteristics of the lawsuit, the client can use litigation as a way of extracting information. I show that, counterintuitively, litigation will occur only when the plaintiff is pessimistic about her prospects at trial. Even if the plaintiff could obtain a higher payoff from bargaining than from litigation-without-bargaining, bargaining may not occur in equilibrium. The plaintiff is more likely to sue if she is more pessimistic about winning damage in court and if litigation is more risky. Litigation is less likely to occur if the plaintiff receives third party financing for litigation.
urn:nbn:de:bvb:19-epub-13208-5
Keywords: C78; D74; D86; K41; 330; settlement-litigation decision; costs of bargaining; non-bargaining; delegation of dispute resolution; risks of litigation; plaintiff-characteristic dependence; low plaintiff win rates; Zivilprozess; Rechtsökonomik; Verhandlungstheorie; Rechtsberatung; Asymmetrische Information; Theorie